2008
DOI: 10.1007/s10832-008-9486-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and electrochemical properties of LiNi1−y Zn y O2

Abstract: Zn doped LiNi 1−y Zn y O 2 (0.00≤y≤0.100) composition was synthesized by an emulsion method. The emulsion-derived powder was calcined at the temperature range of 650∼800°C for 12∼48 h. A single phase of LiNi 1−y Zn y O 2 was obtained at 700°C. The optimum condition for the synthesis of LiNi 1−y Zn y O 2 was to be calcined at 750°C for 36 h in oxygen stream. The composition of LiNi 0.995 Zn 0.005 O 2 showed the largest discharge capacity and improved cycle life. The initial and final discharge capacities were 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Ceramic samples, such as pure and doped BaTiO 3 , under equilibrium conditions at high temperature, generally show a p ‐type to n ‐type change in behaviour on reducing oxygen partial pressure 13, 14. In the p ‐type region, holes are generated by the idealized reaction: …”
Section: Discussionmentioning
confidence: 99%
“…Ceramic samples, such as pure and doped BaTiO 3 , under equilibrium conditions at high temperature, generally show a p ‐type to n ‐type change in behaviour on reducing oxygen partial pressure 13, 14. In the p ‐type region, holes are generated by the idealized reaction: …”
Section: Discussionmentioning
confidence: 99%
“…The inorganic materials, which include AlF 3 , AlPO 4 4 , and Li-Ni-PO 4 , are known to decrease the irreversible capacity and improve the electrochemical performances of OLO materials owing to the enforcement of stability on the surface in the high-voltage region. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The carbon materials, including graphene-based materials, are employed to improve the electronic conductivity of OLO cathode materials. 19,[32][33][34] Also, surface modification by conducting polymers, such as polypyrrole, has been recently reported to provide improved electronic conductivity as well as a thin protective layer on OLO cathode materials.…”
mentioning
confidence: 99%
“…13). In order to improve leakage current characteristics (i.e., enhancement of breakdown strength, of roomtemperature-grown BST thin films), doping the amorphous BST host with acceptor dopants (i.e., Mn, Ni, and Mg) which partially substitute for Ti on the B site of the A 2+ B 4+ O 2− perovskite structure, has been suggested [134][135][136]. On the basis of the similar ionic radii of Ti 4+ (r eff =0.605 Å) and Mg 2+ (r eff =0.72 Å) in sixfold oxygen coordination, we can assume that Ti 4+ is replaced by Mg 2+ in the BST lattice.…”
Section: Perovskite-based Oxide Dielectricsmentioning
confidence: 99%
“…The valence state of an Mg ion is 2+, thus we can expect further reduction in the leakage current density in Mg-doped BST films compared to BST films doped by acceptors with the higher multi-valence states.. Kang et al [134] suggested the potential suitability of a 3 % Mg-doped BST gate insulator for high field-effect mobility (16.3 cm 2 /V · s) TFTs fabricated on PET substrates. Kim et al [136] reported the successful integration of 1 % Ni-doped BST as a gate dielectric for ZnO TFTs exhibiting a very low operation voltage (4 V), field-effect mobility (2.2 cm 2 /V · s), on/off current ratio (1.2×10 6 ), and subthreshold swing (0.21 V/decade). ZnO TFTs with 3 % Mndoped BST showed a field-effect mobility of 1.0 cm 2 /V · s and a low operating voltage of less than 7 V [135].…”
Section: Perovskite-based Oxide Dielectricsmentioning
confidence: 99%